Analisis Pemanfaatan Media Pembelajaran Digital terhadap Minat dan Hasil Belajar Matematika Siswa - Ahda Zahrotun Hasanah; Raras Kartika Sari (Program Studi Pendidikan Matematika, 2025)
The low level of students’ interest and achievement in mathematics due to the limited use of digital learning media motivated this study. This research aimed to analyze the utilization of digital learning media on students’ interest and learning outcomes in mathematics for class XI.3 at SMA Negeri 8 Bandar Lampung. This study employed a quantitative descriptive method supported by qualitative data, involving 25 students of class XI.3 as the research subjects. The research instruments consisted of tests (pretest and posttest), a learning interest questionnaire administered before and after the treatment, and interview sheets to strengthen the data findings. The results showed an increase in the average score of students’ learning outcomes from 57.96 in the pretest to 90.40 in the posttest. In addition, students’ learning interest also increased. Overall, the findings indicate a significant improvement in students’ interest and mathematics learning outcomes after the implementation of digital learning media. Students became more active, motivated, and found it easier to understand mathematical concepts through interactive displays and engaging visual features. The use of digital learning media has a positive impact on improving students’ interest and mathematics learning outcomes.